A responsive architecture an early intervention therapy center for children with Autism Spectrum Disorder (ASD) in Quezon City, Metro Manila - Tan, Reina Ciel P.; Richard Martin E. Rinen (Quezon City College of Architecture, University of the Philippines Diliman, 2023)
In the Philippines, the COVID-19 pandemic has prevented Filipino to access health services and programs because of the deficiency of the current health system and the challenges brought by the pandemic. One of those who have been affected is the children with Autistic Spectrum Disorder (ASD). The pandemic has hindered the development of children with ASD due to the disruption and uncertainty of accessible and safe health facilities and services, physical distancing, and lack of outdoor activities. With that, the
study explored and examined design approaches and solutions for a therapy center for the said children providing them access to health services and an environment with healing and therapeutic experience through the integration of the concept of responsive architecture. To acquire data as bases for the architectural design decisions, interviews with involved health professionals, caretakers, and guardians, an assessment of existing health facilities for children, and a review of related literature were done. The study initially focused on early interventions and treatments (i.e., speech, occupational, and
behavioral therapies through play interaction) and served as a starting point for a facility, envisioned in the future to offer a more holistic program and treatment for the target users. Additionally, the target users were children ages two to 12 years old with ASD and involve pediatric health professionals and therapists. The study also recognizes that the data about the target and involved users, and health facilities may be limited due to data privacy, and confidentiality reasons. Hence, once all data had been collected and
analyzed, the study produced a responsive architectural design through sensory design for an early intervention therapy center for children with ASD in Quezon City, Metro Manila.
include appendices.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Children with autism spectrum disorders -- Quezon City (Metro Manila); Health facilities -- Quezon City (Metro Manila)